The rise of managerialism in international NGOs. Issue 4 (3rd July 2020) - Eagleton-Pierce, Matthew
Abstract: Managerialism has become increasingly incorporated into the practices of international non-governmental organisations (INGOs) in recent decades. To date, IPE has largely failed to examine how and why the managerial ethic has weaved itself into the fabric of prominent INGOs that have a stake in the global economy. The limited IPE literature that has addressed such activity has either cast such changes as part of a culture of professionalisation or as an outgrowth of neoliberalism. This article seeks to question these readings by directly dissecting how managerialism operates within a milieu which has been historically critical of capitalism. The argument is underpinned by conceptual insights from critical management studies, particularly how managerialism is associated with instrumental rationality and control. In relation to international development policy, the article examines the major macro institutional and ideological factors that have encouraged the spread of managerialism. To deepen our understanding of these trends, the article offers new empirics on the struggle over managerialism within Oxfam GB, from a limited imprint in the 1980s to increasing normalisation from the early 2000s. The article calls for IPE to better unmask the internal politics of INGOs and, in turn, connect such evidence to wider structural tendencies.